Disparities in technology utilization among youth with type 1 diabetes across diverse racial and socioeconomic backgrounds - Rozalina G McCoy; Tamim Rajjo; Herbert C Heien; Alaa Al Nofal; Doha Hassan (BMJ Open Diabetes Research & Care)
Background Previous studies have demonstrated disparities in the utilization of diabetes technology among youth with type 1 diabetes (T1D) based on race and socioeconomic status (SES). Few studies have examined these differences on a national scale or among youth with commercial health insurance.Aim To investigate differences in the fill rates of insulin pumps and continuous glucose monitors (CGMs) among commercially insured children with T1D across diverse racial and SES groups.Methods Using medical and pharmacy claims included in the OptumLabs Data Warehouse, we calculated the proportion of youth <18 years with T1D who had a fill for an insulin pump or a CGM, overall and stratified by race/ethnicity and annual household income, between 2011 and 2021.Results Among 13,246 youth with T1D, 36.1% had CGM and 30.9% had pump fills. White youth had higher CGM and pump fills than black (CGMs: 35.8% vs 22.5%; pumps: 31.9% vs 21.2%, p<0.001) and Hispanic (CGMs: 35.8% vs 32.6%, p=0.047; pumps: 31.9% vs 25.0%, p<0.001). Youth from households with income <US$40,000 had lower CGM and pump fills than those with income ≥US$200,000 (CGM 25.4% vs 43.8%; pumps: 22.4% vs 38.8%, p<0.001). Within similar incomes <US$40,000, black youth had fewer CGM and pump fills than white youth (CGM: 15.2% vs 27.9%, p=0.006; pumps: 12.9% vs 25.5%, p=0.004). This racial difference disappeared with income ≥US$200,000 (CGMs: 47.5% for black vs 43.1% for white; pumps: 45.9% for black vs 38.3% for white, p=0.45 and p=0.57, respectively).Conclusions In a cohort of commercially insured youth with T1D, both race and income are important factors that can independently influence the use of diabetes technology. Racial disparities decrease with higher income and disappear at incomes ≥US$200,000. Black youth with income <US$40,000 are at the highest exclusion risk from essential technologies. Greater effort is needed at both the system and individual levels to mitigate these disparities.